2014
DOI: 10.1103/physrevlett.112.164802
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of a Tunable Microwave Undulator

Abstract: Static magnetic undulators used by x-ray light sources are fundamentally too limited to achieve shorter undulator periods and dynamic control. To overcome these limitations, we report experimental demonstration of a novel short-period microwave undulator, essentially a Thomson scattering device, that has yielded tunable spontaneous emission and seeded coherent radiation. Its equivalent undulator period (λ u) is 13.9 mm while it has achieved an equivalent magnetic field of 0.65 T. For future-generation light so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 17 publications
0
49
0
Order By: Relevance
“…Undulators with periods less than or on the order of a millimeter, often referred to as micro-undulators, are, therefore, of great interest. Several micro-undulator ideas have been proposed including electro-static undulators [3,4], crystalline undulators [5], RF-based [6], laser-plasma-based [7][8][9], and optical undulators [10][11][12][13][14][15][16][17]. In this Letter we propose a micro-undulator based on controlling the transverse forces experienced by an electron beam inside a laserexcited plasma channel.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Undulators with periods less than or on the order of a millimeter, often referred to as micro-undulators, are, therefore, of great interest. Several micro-undulator ideas have been proposed including electro-static undulators [3,4], crystalline undulators [5], RF-based [6], laser-plasma-based [7][8][9], and optical undulators [10][11][12][13][14][15][16][17]. In this Letter we propose a micro-undulator based on controlling the transverse forces experienced by an electron beam inside a laserexcited plasma channel.…”
mentioning
confidence: 99%
“…(The equation of motion in the transverse direction orthogonal to the laser beam centroid motion is d 2 y/dz 2 + k 2 β y = 0.) The transverse momentum of the electron is (6) where k u = 1/Z R , ψ β is a phase determined by the electron injection relative to the laser beam centroid oscillation,…”
mentioning
confidence: 99%
“…It has recently been experimentally demonstrated that electron optics can, in principle, also be replaced by plasma technology [6][7][8], leaving the undulator as the only major factor defining the size of the facility. Several ideas for undulators with periods on the order of millimeter or below (often referred to as microundulators) have been proposed, including electrostatic [9,10], crystalline [11][12][13], microwave [14], plasma [15], nano-wire [16] and laserbased [17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…1(b), principally to avoid the size and complexity of the resonant ring, but also to provide flexibility in operating conditions for different levels of beam loading. The standing-wave cavity designs can offer comparable RF-to-beam efficiencies, since a standing wave is the superposition of two counter-propagating travelling waves; wall losses are similar when taking into account the extra length of the resonant ring; and high cavity end-wall losses can be mitigated [10].…”
Section: -2mentioning
confidence: 99%